Effect of Change in Physical Parameters in the Paddling Response of the Common Backswimmer (Notonecta glauca) - Krishnan, Jithu U.; G. K., Surya Narayanan (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This study investigates the impact of varying environmental factors, specifically temperature, pH, and white light intensity, on the paddling response of the common backswimmer, Notonecta glauca Linnaeus 1758 (Hemiptera: Notonectidae). The normal paddling rate was established at approximately 31.6 flaps per minute (FPM) under controlled conditions of 30°C, pH 6.8, and 50% sunlight exposure. When exposed to increased pH levels, the paddling rate exhibited a significant increase, rising by nearly 75% compared to the normal rate. Conversely, a decrease in pH led to an even greater enhancement in paddling activity, with a rise of approximately 90%. A notable response was observed under increased temperature, where the paddling rate surged by more than 2.6 times than expected, indicating a strong sensitivity to thermal changes. The most reduction in paddling activity occurred under low light intensity, with the rate plummeting to roughly 37% of the normal value. The findings underscore the susceptibility of N. glauca to variations in these key environmental parameters, particularly highlighting its heightened response to temperature fluctuations and low light conditions. The species of interest is observed as ecological sentinels and understanding its optimum limit of tolerance over fundamental physical parameters enables us to estimate the effect of climate change, environmental modifications and habitat alterations over the course of time.